ANALISIS PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MIND MAPPING TERHADAP HASIL BELAJAR SISWA SD - Asri Nurjanah; Dalifa Dalifa; Feri N Noperman (JURIDIKDAS, 2020)
This study aims to re-analyze the use of the Mind Mapping cooperative learning model in improving learning outcomes for elementary school students. This study uses a meta-analysis method. The population in this study is the result of research on the influence of the mind mapping type cooperative learning model in eight journals that have been published nationally in Indonesia. The sample of this research was five national journals published in the period 2010-2020 at the elementary school level, namely experimental research on the effect of the mind mapping type cooperative learning model on learning outcomes of elementary school students. The data analysis technique uses documentation data, namely in the form of searching for relevant articles related to the effect of the mind mapping cooperative learning model. The data analysis technique uses the power of the learning model (N-Gain), the mean, and the hypothetical test. Based on the big analysis the most influential in total get an average value of 54.5 with the medium effect category. The results of the analysis by calculating the t-test value also show that the mind mapping type of cooperative learning model has an effect on learning outcomes. Judging from the value of tcount (10.684)> ttable (1.89), the tcount value obtained is higher than the ttable value, so the mind mapping type cooperative learning model shows an effect on the learning outcomes of elementary school students.